Exploring resource preservation dynamics in Portuguese business expatriates: The qualifying role of company policies. - Coelho, J. V. (18th International Conference on Interdisciplinary Social Science, 2023)
Business expatriates can gain resources conducive to their work-related motivation and willingness (to go), particularly through organizational support and policy measures (Biswas, Mäkelä & Maike, 2021). Considering resource conservation (COR) and resource dynamics as contingent on supportive vs. undermining organizational conditions, the study that is presented examined the role of expatriate company policies as job resource or passageway that enables expatriate willingness (to go).